Muzykoterapia i jej właściwości w usprawnianiu dziecka z autyzmem - Knapik-Szweda, Sara (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The article presents the outlines of the research and the conclusions based on the author’s PhD dissertation. It touches upon the influence of music therapy techniques on the improvement of a development of autistic children, especially in terms of communication as well as their social, cognitive, emotional and behavioral development. The researcher presents and compares two undirective methods: Music therapy and Growth through Play System (GPS). Among many therapeutic applications of music, the most significant ones are chosen and analysed: improvisation, re-creation, composition and listening associated with musical relaxation. The results are presented in the form of an evaluation which therapy is the most beneficial for autistic children and their holistic development.